Acute Cholecystitis Caused by Ceftriaxone Stones in an Adult - Christian D. Becker; Robert A. Fischer (Case Reports in Medicine)
Acute cholecystitis is a major health problem. There are multiple etiologies to be considered and early recognition of the condition is important to optimize management and outcome. We report the first case in the medical literature of symptomatic acute cholecystitis triggered by ceftriaxone-associated gallbladder sludge formation and, importantly, solid ceftriaxone gallstone formation in an adult patient with underlying mineral and pigment cholecystolithiasis, necessitating cholecystectomy. This case serves as a reminder for physicians to keep this uncommon cause of cholecystolithiasis and cholecystitis in mind in patients who receive prolonged ceftriaxone therapy. These patients should be cautioned to promptly report to their physicians any signs or symptoms of cholecystitis in order to ensure timely and appropriate evaluation.